THE CORRELATION BETWEEN STUDENTS’ CRITICAL THINKING SKILLS AND THEIR READING COMPREHENSION AT UNDERGARDUATE STUDY PROGRAM ENGLISH DEPARTMENT FACULTY OF LANGUAGES AND LITERATURE UNIVERSITAS NEGERI MAKASSAR - Nurul Ramadhani; Kisman Salija; Sultan Baa (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The study's goal was to determine the level of students' critical thinking skills, the level of students' reading comprehension, the classification of the students' critical thinking skills toward the students' reading comprehension, and whether there was a significant correlation between students' critical thinking skills and their reading comprehension. The study used quantitative methods, specifically a correlational study. The participants were from the English Education Study Program of fifth semester students at Universitas Negeri Makassar. The study's findings revealed that critical thinking skills were significantly correlated with reading comprehension using Pearson Product Moment analysis. This study clearly revealed that most students had a high proclivity for critical thinking while reading English texts, which included interpretation, analysis, evaluation, inference, explanation, and self-regulation. Thus, the results show that Students who think critically are more creative and critical in their understanding of ideas